Formulation, characterization and cytotoxicity evaluation of orotic acid and magnesium orotate loaded into gum Arabic and chitosan nanoparticles for drug delivery - Abdelkader, Hassani (2020)
Controlled drug release has been used to improve the bioavailability properties of various drugs. These systems enable better regulation of drugs administered for treatments and reduce their side effects in therapeutic levels with minimum concentrations. In this study, gum arabic )GA( and chitosan (CS) nanoparticles were used as nanocarriers to encapsulate orotic acid (OA) and magnesium orotate (MgOr) due to their attractive physicochemical properties which can improve targeted drug delivery. Therefore, the main objectives of the current study were to develop a nanomaterial-based carrier as a novel drug delivery system of OA and MgOr by using gum arabic nanoparticles )GANPs( and chitosan nanoparticles )CSNPs( for enhanced delivery efficiency. Then, the antioxidant and in vitro antihypertensive properties of the nanoparticles (NPs) were assessed. Comparisons were made between active compounds, respective polymers and synthesised nanopartilces )NPs( in terms of their antioxidant, antihypertensive and cytotoxicity properties. The resulting four NPs, namely MgOrGANPs, MgOrCSNPs, OAGANPs and OACSNPs, were prepared using the freeze-drying technique. The physicochemical characteristics of NPs, specifically the functional groups, crystallinity, thermal behaviour, surface morphology, and drug loading percentage, were examined using Fourier-transform infrared spectroscopy )FTIR(, X-ray diffractometry )XRD(, differential scanning calorimetry )DSC(, and transmission electron microscopy )TEM(. Furthermore, the antioxidant potential activities of orotic acid nanoparticles )OANPs( and magnesium orotate nanoparticles )MgOrNPs( were assessed using 1,1-diphenyl-2-picrylhydrazyl )DPPH(, nitric oxide )NO(, and β-carotene bleaching assays. Apart from that, the antihypertensive activity was performed using angiotensin-converting enzyme )ACE(. In addition, HepG2 )human liver cancer cell lines(, MCF7 )human breast cancer cell lines(, HT29 )human colon cancer cell line(, MCF10A )normal breast cell lines (, ARPE-19 )human retinal epithelial cell line(, and 3T3 )mouse fibroblast cell line( were treated with NPs for cytotoxicity evaluation. Meanwhile, The FTIR, XRD and DSC analysis confirmed the encapsulation of OA and MgOr into GA/CSNPs. The initial burst of drugs was improved with polymer coating agents, resulting in their controlled release of drugs from their nanoparticles. On the other hand, the preliminary in vitro cytotoxicity tests suggested that OANPs and MgOrNPs were not acutely toxic and significantly inhibit the growth of cancer cells. Thus, the findings demonstrated that polymer coating significantly improved the antioxidant, antihypertensive and cytotoxicity properties of drug-loaded nanoparticles compared to the uncoated ones. In conclusion, the desirable characteristicsof of the OANPs and MgOrNPs that were developed in this study have the potential as drug nanocarriers to deliver poorly water-soluble drugs OA and MgOr.